PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI A SDN 011 BUKIT GAJAH KECAMATAN UKUI - Rohlina Tambunan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
The background of this study is the low student learning outcomes IPA. Of the 20 students, only 7 students (42.31%) completed the study results, while the average student learning outcomes is only 65.38. This study aims to improve science learning outcomes of students with the application of quantum teaching learning model. This research is a class act. Based on the results of the study revealed that the learning outcomes and the activities of teachers and students has increased, the average value of the basic score 65.38 UH then the first cycle to 69.08 with an increase of 5.66%. While on the second cycle into 85.54 with an increase of 23.83%. In the first cycle of the first meeting 66.7% (enough), at a meeting II increased to 75% (good). In the second cycle the first meeting 83.3% (good), then at a meeting II increased to 95.8% (excellent). While the percentage of student activity also increased. In the first cycle of the first meeting 62.5% (enough), at a meeting II increased to 70.8% (good). In the second cycle the first meeting 79.2% (good), then at a meeting II increased to 91.7% (excellent).